The poor in England, 1700-1850 : an economy of makeshifts - King, Steven (2003)
Introduction / Alannah Tomkins, Steven King. - 'Not by bread only'? Common right, parish relief and endowed charity in a forest economy, c. 1600-1800 / Steve Hindle. - Economy of makeshifts and the poor law: a game of chance? / Margaret Hanly. - 'Agents in their own concerns'? Charity and the economy of makeshifts in eighteenth-century Britain / Sarah Lloyd. - Crime, criminal networks and the survival strategies of the poor in early eighteenth-century London / Heather Shore. - Pawnbroking and the survival strategies of the urban poor in 1770s York / Alannah Tomkins. - Kinship, poor relief and the welfare process in early modern England / Sam Barrett. - Making the most of opportunity: the economy of makeshifts in the early modern north / Steven King –Conclusion / Steven King, Alannah Tomkins